(untitled) (Asian Journal of Medical and Biological Research, 2021)
Toxicological evaluation of herbal medicines is necessary because of possible adverse effects that may be associated with their consumption. This study screened antimalarial herbal recipe (containing leaves of Azadirachta indica and stem-bark of Alstonia boonei) and its individual plant’s extract for DNA and chromosomes mutation potentials following the DNA fragmentation and Allium cepa assays. Superoxide dismutase (SOD), catalase (CAT) and malondialdehyde (MDA) activity of the recipe and each extract was determined. The kinds of phytochemicals present in them were determined using the FTIR technique. Water extracts of A. indica, and A.boonei at all the tested doses caused significantly lower DNA fragmentations than those of the controls. However, at 25.0% and 50.0% recipe, there was no significant difference in the percentage fragmented DNA compared to the positive control (0.05% sodium azide). Cell division was significantly inhibited by the extracts and recipe, chromosomal aberrations were not dose dependently induced and were significantly lowered than that caused by sodium azide (positive control). The individual extracts and their recipe significantly inhibited Root growth. However, 12.5% recipe promoted root growth that was not significantly different from that of distilled water (negative control). SOD and CAT activities of each of the extracts and their recipe were dose dependent and significantly higher than those of the controls. Water extract of A. indica significantly suppressed generation of malondialdehyde compared to water extract of A. boonei and recipe as well as the control. The individual extracts and their recipe contained phenolic phytochemicals. The obtained results show that extract of A. indica, A. boonei and their recipe have good antioxidant properties with strong mitodepressive and root growth inhibitory effects except at 12.5% recipe. However, A. indica extract seems to have least cyto-muta-genotoxic effects than water extract of A. boonei and the recipe in mice and A. cepa cells. Asian J. Med. Biol. Res. 2021, 7 (3), 249-259